A Variação da Dívida Pública Brasileira entre 1995 e 2005 - Fatores Determinantes - Castro, Francisco Januário de (2007)
This dissertation makes an analysis of the main causing factors of the variation of the Brazilian public debt between 1995 and 2005. Firstly, it is discoursed on the approaches of the new classics, Keynesians and the neo-classic synthesis about the public debt. It is presented, after that, the evolution of the privatizations, primary surplus, growth of the GDP, acknowledgment of debts and exchange depreciations. In the sequence, the result of each one of these factors is brought up to date by the IPCA until December of 2005 and by paid the average tax of interests on the public debt in each year. It is made a comparison of the interests paid on the public debt of Brazil with the interest rate Real practiced at the countries developed added of IPCA of Brazil resulting in a great difference, what is determined our public debt was remunerated with real interests same to the real interest rates of the developed countries would have paid of interests 68,55% than indeed we paid. It concludes that, in reason of the high average tax of interests for which the debt was remunerated in the period, the described factors above make influence more strongly than its results presented in current values. The main obstacle to the fall of the debt, in absolute terms, is the high taxes of interests for which it is remunerated